Interaction of Cr(VI) reduction and denitrification by strain Pseudomonas aeruginosa PCN-2 under aerobic conditions. (June 2015) - He, Da; Zheng, Maosheng; Ma, Tao; Li, Can; Ni, Jinren
Highlights: Simultaneous aerobic Cr(VI) and nitrate reduction was achieved by strain PCN-2. Coordinate presence of gene ChrR, napA, nirS, cnorB and nosZ was confirmed. Cr(V) detection confirmed Cr(VI) reduction via initial single-electron transfer. Cr(VI) and nitrate reduction occurred faster at higher cell amount and pH 8–9. Increasing Cr(VI) inhibited aerobic denitrification and N2 O reduction. Abstract: Inhibition of efficient denitrification in presence of toxic heavy metals is one of the current problems encountered in municipal wastewater treatment plants. This paper presents how to remove hexavalent chromium (Cr(VI)) and nitrate simultaneously by the novel strain Pseudomonas aeruginosa PCN-2 under aerobic conditions. The capability of strain PCN-2 for Cr(VI) and nitrate reduction was confirmed by PCR analysis of gene ChrR, napA, nirS, cnorB, nosZ, while Cr(VI) reduction was proved via an initial single-electron transfer through Cr(V) detection using electron paramagnetic resonance. Experimental results demonstrated that Cr(VI) and nitrate reduction by strain PCN-2 was much faster at pH 8–9 and higher initial cell concentration. However, increasing Cr(VI) concentration would inhibit aerobic denitrification process and result in an significant delay of nitrate reduction or N2 O accumulation, which was attributed to competition between three electron acceptors, i.e., Cr(VI), O2 and nitrate in the electron transport chain.